2021
DOI: 10.1111/acer.14697
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific effect of prenatal alcohol exposure on N‐methyl‐D‐aspartate receptor function in orbitofrontal cortex pyramidal neurons of mice

Abstract: Background: Alcohol consumption during pregnancy can produce behavioral and cognitive deficits that persist into adulthood. These include impairments in executive functions, learning, planning, and cognitive flexibility. We have previously shown that moderate prenatal alcohol exposure (PAE) significantly impairs reversal learning, a measure of flexibility mediated across species by different brain areas that include the orbital frontal cortex (OFC). Reversal learning is likewise impaired by genetic or pharmaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
3
6
0
Order By: Relevance
“…Therefore, potential contributors to MSI are the N ‐methyl‐ d ‐aspartate receptor (NMDAr) and γ‐aminobutyric acid receptor (GABAr). Interestingly, both can be affected by developmental alcohol exposure (Licheri et al, 2021; Savage et al, 1992; Smiley et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, potential contributors to MSI are the N ‐methyl‐ d ‐aspartate receptor (NMDAr) and γ‐aminobutyric acid receptor (GABAr). Interestingly, both can be affected by developmental alcohol exposure (Licheri et al, 2021; Savage et al, 1992; Smiley et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, recent work has observed that moderate PAE influences the firing characteristics of spatially tuned hippocampal cells, such that the prominence of firing in relation to environmental position is reduced (Harvey et al, 2020). PAE can also induce structural and functional changes in other neural systems involved in spatial behavior including the medial septum (Moore et al, 1997), anterior cingulate cortex (Moore et al, 1998), and orbitofrontal cortex (Licheri et al, 2021). These changes in hippocampal, cortical, and subcortical function likely contribute to observed impairments in spatial information processing.…”
Section: Introductionmentioning
confidence: 99%
“…A separate cohort of 18 mice (4–5 animals for each experimental group) from eight SAC and eight PAE litters were used for electrophysiological studies. These mice had ad libitum access to food as previously described (Licheri et al., 2021) as food restriction in mice or rats can alter cortical GABAergic transmission (Dazzi et al., 2014; Yang et al., 2016). In all cases, the investigators were blind to the treatment group assignments.…”
Section: Methodsmentioning
confidence: 99%